Dopamine and Citicoline-Co-Loaded Solid Lipid Nanoparticles as Multifunctional Nanomedicines for Parkinson's Disease Treatment by Intranasal Administration - Stefano Castellani; Giorgia Natalia Iaconisi; Francesca Tripaldi; Vito Porcelli; Adriana Trapani; Eugenia Messina; Lorenzo Guerra; Cinzia Di Franco; Giuseppe Maruccio; Anna Grazia Monteduro; Filomena Corbo; Sante Di Gioia; et al. (MDPI AG, 2024)
This work aimed to evaluate the potential of the nanosystems constituted by dopamine (DA) and the antioxidant Citicoline (CIT) co-loaded in solid lipid nanoparticles (SLNs) for intranasal administration in the treatment of Parkinson disease (PD). Such nanosystems, denoted as DA-CIT-SLNs, were designed according to the concept of multifunctional nanomedicine where multiple biological roles are combined into a single nanocarrier and prepared by the melt emulsification method employing the self-emulsifying Gelucire® 50/13 as lipid matrix. The resulting DA-CIT-SLNs were characterized regarding particle size, surface charge, encapsulation efficiency, morphology, and physical stability. Differential scanning calorimetry, FT-IR, and X ray diffraction studies were carried out to gain information on solid-state features, and in vitro release tests in simulated nasal fluid (SNF) were performed. Monitoring the particle size at two temperatures (4 °C and 37 °C), the size enlargement observed over the time at 37 °C was lower than that observed at 4 °C, even though at higher temperature, color changes occurred, indicative of possible neurotransmitter decomposition. Solid-state studies indicated a reduction in the crystallinity when DA and CIT are co-encapsulated in DA-CIT-SLNs. Interestingly, in vitro release studies in SNF indicated a sustained release of DA. Furthermore, DA-CIT SLNs displayed high cytocompatibility with both human nasal RPMI 2650 and neuronal SH-SY5Y cells. Furthermore, OxyBlot assay demonstrated considerable potential to assess the protective effect of antioxidant agents against oxidative cellular damage. Thus, such protective effect was shown by DA-CIT-SLNs, which constitute a promising formulation for PD application.